Deoxyguanosine Factors and Protein Carbonyl Groups as Markers ofOxidative Stress in the Fasting Individuals in Tehran - Abdolhossein Bastani; Fatemeh Azadmanesh; Mohammad Hassan Heidari; Reza Haji Hosseini Baghdadabadi (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: Oxidative stress represents an imbalance between the production of reactive oxygen species and a biological system's ability to readily detoxify the reactive intermediates or to repair the resulting damage. Calorie restriction canreduce the damages caused by oxidative stress. Materials and Methods: The subjects, who were healthy males and females able to fast for a month, were randomly selectedfrom the staff of Hippocrates and Imam Khomeini hospitals. Samples of their serum and urine were collected three times, i.e. 4 days before fasting as control, on the 14th day of fasting, and on the 29th day of fasting. Plasma malondialdehyde levels were measured using HPLC technique, while the levels of protein carbonyl groups in plasma, and the levels of 8-iso prostaglandin F2α and 8-hydroxy-2'-deoxyguanosine in urine were measured by ELISA technique. The data were analyzed using SPSS, t test  paired samples, Independentttest the level of statistical significance was considered to be p <0.05. Results: Totally, 60 subjects participated in the study, where seven participants were male (11%) and 53 subjects (89%) were female. Mean and SD of the age of the participants were 37±10 years. Concentrations of plasmamalondialdehyde and 8-iso prostaglandin F2α in urine showed a significant decrease during fasting in Ramadan in all subjects compared with the control samples; moreover, their levels in the third sampling round were significantly lower than that in the second one (p < 0.01). Conclusion: Since plasma levels of MDA and urin levels of 8-isoPGF significantly were decreased during fasting in Ramadan.It seems that fasting a month decreased  oxidative stress.  we hope that with more study in future ,we can use  Ramadan fasting as a natural way to protect human against  different disease which  oxidative stress is involved. Keywords: Fasting, Malondialdehyde, 8-iso prostaglandin F2α, 8-hydroxy-2-deoxyguanosine, Protein carbonyl For downloading the full-text of this article please click here.